NORMALISASI KEKERASAN DI RUANG SEKOLAH: BULLYING SEBAGAI FENOMENA SOSIAL YANG DIREPRODUKSI - Yansen Kobo, Arnoldus; Da’o Lada, Bertolomeus; Dua Raga, Brigitha Viviana; Mario Sasi, Venantius; Maria, Joannes George; Opat, Remigius (STKIP Subang, 2026)
Bullying is a form of peer violence that continues to occur frequently in school settings and exhibits a recurring pattern over time. This phenomenon is not only related to individual behavior but also to social structures, school culture, and patterns of power relations that develop within educational institutions. This study aims to analyze bullying as a form of the normalization of violence that is reproduced through social interactions and the school system. A qualitative approach based on a literature review was used to examine empirical literature and current social theories, utilizing Weinberg’s three-stage framework: problem identification, diagnosis of causes, and solution. The results indicate that bullying is influenced by family dynamics, peer group pressure, children’s characteristics, and weaknesses in school supervision mechanisms. The normalization of violence occurs when bullying is considered commonplace or becomes part of traditions such as seniority, thereby reinforcing the reproduction of violence in students’ daily interactions. This study emphasizes that addressing bullying requires a comprehensive approach through individual interventions, strengthening the role of families, enhancing teachers’ capacities, and transforming school culture to create a safe, inclusive, and violence-free learning environment.